(untitled) (INNOVATIVE ECONOMY, 2022)
Brych V.Ya., Putsenteilo P.R., Hunko S.I. DEVELOPMENT OF CRITICAL TECHNOLOGIES IN THE FIELD OF ENERGY SECURITY OF UKRAINE Purpose. A study of approaches to understanding the essence of the concept of “critical technologies”, an overview of the development of critical technologies in the field of energy security of Ukraine and an outline of the features of their use in modern conditions and for the future. Methodology of research. The methodological basis of the research is the dialectical method of scientific knowledge. General scientific and special methods were used in the research process, in particular: analysis and synthesis, dialectical – to determine the initial conditions and content of critical technologies; analytical – when processing literary and Internet sources; causal – to determine the dynamics of the development of the energy sector of Ukraine; abstract and logical – for outlining the main directions of functioning of critical technologies in the field of energy security, forming conclusions and proposals. Findings. Current and prospective critical technologies in the energy sector are summarized, which will be able to ensure the increase in the efficiency of the use of resources of the fuel and energy complex and ensure the comprehensive energy security of Ukraine. The impact of renewable energy sources is considered as a key parameter of the energy transition from the traditional use of energy resources to an innovative one, which can lead to the greening of the energy sector and the formation of an innovative and breakthrough model of the green economy. Originality. Measures to increase generation from renewable energy sources have been substantiated, which will make it possible to strengthen Ukraine’s energy independence and contribute to the implementation of the Green Energy Course. A list of promising critical energy technologies in the field of energy security of Ukraine is proposed. Practical value. The substantiated research results can be used to form a list of the latest critical technologies in the field of energy security as an important component of Ukraine’s national security. Key words: energy, energy security, critical technologies, innovations, energy strategy of Ukraine, energy supply, renewable energy sources, wind power plant, solar power plant.